2013
DOI: 10.1086/674758
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Erythropoietin and Sildenafil Can Effectively Attenuate Hypoxia‐Induced Pulmonary Hypertension in Mice

Abstract: Pulmonary hypertension (PH) is an incurable disease that often leads to right ventricular hypertrophy and right heart failure. This study investigated single versus combined therapy with sildenafil and erythropoietin on hypoxia-induced pulmonary hypertension in mice. Mice were randomized into 5 groups and exposed to either hypoxia (10% oxygen) or normoxia for a total of 5 weeks. Hypoxic mice were treated with saline solution, erythropoietin (500 IU/kg 3 times weekly), sildenafil (10 mg/kg daily), or a combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
(49 reference statements)
2
1
0
Order By: Relevance
“…At present, rhEPO is used to treat anemia, including early and late anemia due to premature birth, and the administration of rhEPO has proven to be both feasible and safe in neonates. In addition, co‐treatment of EPO and sildenafil (a phosphodiesterase type five inhibitor) showed a synergetic effect in a murine model of hypoxia‐induced PH . Taken together, these present and previous findings suggest that EPO treatment is safe and beneficial as a postnatal therapy for PH and lung injury for infants with CDH.…”
Section: Discussionsupporting
confidence: 75%
“…At present, rhEPO is used to treat anemia, including early and late anemia due to premature birth, and the administration of rhEPO has proven to be both feasible and safe in neonates. In addition, co‐treatment of EPO and sildenafil (a phosphodiesterase type five inhibitor) showed a synergetic effect in a murine model of hypoxia‐induced PH . Taken together, these present and previous findings suggest that EPO treatment is safe and beneficial as a postnatal therapy for PH and lung injury for infants with CDH.…”
Section: Discussionsupporting
confidence: 75%
“…Erythropoietin has also been associated with vascular remodeling and smooth muscle proliferation in the pulmonary vasculature (Karamanian et al, 2014). Higher serum erythropoietin has been correlated with pulmonary arterial hypertension in humans (Karamanian et al, 2014) and erythropoietin administration has been shown to blunt hypoxia-induced pulmonary hypertension in mice (Samillan et al, 2013). A correlation between higher EPO levels and higher PASP was also seen in this study.…”
supporting
confidence: 76%
“…As previously described ( Voituron et al, 2009 ; Niane et al, 2011 ; Samillan et al, 2013 ; Jeton et al, 2022 ), breathing variables were measured non-invasively in unanesthetized and unrestrained animals using whole-body flow barometric plethysmograph (Emka technologies, Paris, France). This method consists of measuring the pressure variations in a recording chamber during spontaneous ventilation.…”
Section: Methodsmentioning
confidence: 99%